PEMBERDAYAAN MASYARAKAT DALAM DUNIA PENDIDIKAN - Henni Sukmawati (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2018)
The quality of human resources in a region, depends not only on the efforts made by the school, but also depends on the level of community participation on education. The higher the level of community participation on education in a region, the more advanced the human resources in the area and vice versa, the lower the level of public participation towards education in a region, the more retreats of human resources in the area.